Laminated film and its use

By adjusting the cutting and yield stress of the transparent layer of stacked membrane adhesion to 0.15N/mm2, the problem of the edge line marks during the punching processing is solved, and the resistance of the punch is resistant to ensure that the image should not change in the narrow border display.

CN115122725BActive Publication Date: 2025-01-24DAICEL CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210300369.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-24
Filing Date
2022-03-24
Publication Date
2025-01-24
Estimated Expiration
2042-03-24

AI Technical Summary

Technical Problem

The existing transparent laminated films are prone to edge marks during punching and cutting, and especially in narrow-bezel displays, which leads to image strain, which becomes a problem.

Method used

By adjusting the shear and yield stress of the adhesive layer to more than 0.15N/mm2, it improves the punching of the layer of the diaphragm, thereby suppressing the production of the edge line marks.

Benefits of technology

It is realized that it does not produce or significantly reduce the edge marks in the punching processing, ensuring that the image does not produce a strain in the narrow bezel display, which improves the display effect of the display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115122725B_ABST
    Figure CN115122725B_ABST
Patent Text Reader

Abstract

The present invention provides a laminated film having punch mark resistance. The laminated film comprises a substrate layer, a release layer, and an adhesive layer sandwiched between the substrate layer and the release layer, wherein the shear yield stress of the adhesive layer when a strain is applied at 5 mm / min in a direction parallel to the film surface is adjusted to 0.15 N / mm 2 The shear yield stress may be 0.17 N / mm 2 The above. It may be that the laminated film is a transparent film. It may be that the adhesive layer contains an optically transparent adhesive. It may be that the optically transparent adhesive is a cured product of a curable composition. It may be that the curable composition contains a (meth) acrylic polymer and a crosslinking agent. It may be that the substrate layer contains a transparent resin. It may be that the laminated film is a film for punching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated film having punch-cut resistance and use thereof. Background Art

[0002] Conventionally, as described in Japanese Patent Application Laid-Open No. 2015-98123 (Patent Document 1), a transparent laminated film including a substrate layer, an optical functional layer, a cover layer, and an adhesive layer (or bonding layer) is used as an optical film provided on the display surface of various display devices such as personal computer (PC) monitors, televisions, and smartphones. In the transparent laminated film, the adhesive layer is formed of an optically clear adhesive (OCA: Optically Clear Adhesive).

[0003] As a method for molding a transparent laminated film into a target display size, punching is used. In the past, in the punching process of a transparent laminated film, it is known that there is a phenomenon in which a slight deformation occurs on the inner side of the film end along the punching shape. This deformation is called an edge line mark (TM: touring mark), which is produced, for example, due to temporary deformation of the adhesive layer during the punching process, and occurs near the end of the film (near the cut portion) in the form of a linear mark along the end. Therefore, in existing display devices, the existence of the edge line mark is hidden by the frame of the display, and it does not become a serious problem. However, in recent years, with the narrowing (thinning) of the frame of displays (monitors), the edge line mark has become a problem because the edge line mark is obviously present on the display, causing the image to be strained.

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-98123 Summary of the invention

[0006] Problems to be solved by the invention

[0007] However, as for the existing adhesives (or adhesives) such as OCA, as their design criteria, the optical properties, viscoelastic properties, and adhesion are mainly concerned, and there is no design based on the viewpoint of suppressing punching marks. In addition, the inventors studied the correlation between the generation of punching marks and the adhesion of the adhesive, and the results clearly showed that there is no correlation between these properties and the generation of punching marks.

[0008] Therefore, an object of the present invention is to provide a laminated film having punch mark resistance and use thereof.

[0009] Solutions for solving problems

[0010] The present inventors have found that by adjusting the shear yield stress (or yield shear stress) of the adhesive layer (or bonding layer) of the laminated film to 0.15 N / mm 2As described above, the punching mark resistance was achieved, thereby completing the present invention.

[0011] That is, the laminated film of the present invention is a laminated film comprising a substrate layer, a release layer, and an adhesive layer interposed between the substrate layer and the release layer, and the shear yield stress of the adhesive layer when a strain is applied at 5 mm / min in a direction parallel to the film surface is 0.15 N / mm 2 The shear yield stress can be 0.17N / mm 2 The above. It may be that the adhesive layer contains an optically transparent adhesive. It may be that the optically transparent adhesive is a cured product of a curable composition. It may be that the curable composition contains a (meth) acrylic polymer and a crosslinking agent. It may be that the substrate layer contains a transparent resin. It may be that the laminated film is a film for punching. It may be that the laminated film is a punched film formed by punching.

[0012] The present invention also includes a method for producing a punched film, which comprises punching the laminated film to produce the punched film.

[0013] The present disclosure also includes a display device, which has the punched film on its display surface. The display device may be a narrow-frame display.

[0014] The present invention also includes a method for improving the punch mark resistance of a laminated film, wherein the shear yield stress of the laminated film comprising a substrate layer, a release layer, and an adhesive layer sandwiched between the substrate layer and the release layer is adjusted to 0.15 N / mm2 when a strain of 5 mm / min is applied to the adhesive layer in a direction parallel to the film surface. 2 As described above, the punch cut resistance of the laminated film is improved.

[0015] It should be noted that in the scope of this specification and claims, "resistance to punching marks" refers to the following film properties, namely, no punching marks such as edge line marks are produced, or even if punching marks are produced, they are produced near the ends of the film, and even for narrow-frame (thin-frame) displays, the image will not be strained.

[0016] In addition, in the present specification and the scope of claims, a "narrow frame display" refers to a display having a narrow width of a frame portion (a border portion around a screen) of a display device.

[0017] Furthermore, in the scope of the present specification and claims, the "punching surface" refers to the surface on the side where the punching blade first contacts the laminated film.

[0018] Effects of the Invention

[0019] In the present application, the shear yield stress of the adhesive layer of the laminated film [specifically, the maximum stress when the adhesive layer is displaced in the film surface direction (transverse shear)] is adjusted to 0.15 N / mm 2 As described above, punch cut resistance can be imparted to the laminated film. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 These are a schematic side view (a) and a top view (b) of a sample used for measuring the shear yield stress of an adhesive layer in Examples. DETAILED DESCRIPTION

[0021] [Laminated film]

[0022] The laminated film of the present invention includes a substrate layer, a release layer, and an adhesive layer (or pressure-sensitive adhesive layer) interposed between the substrate layer and the release layer.

[0023] (Adhesive layer or bonding layer)

[0024] In the laminated film of the present invention, the shear yield stress (or maximum value of stress) when the adhesive layer is strained at 5 mm / min in a direction parallel to the film surface is 0.15 N / mm 2 Above (e.g. 0.15N / mm 2 ~1N / mm 2 ), preferably 0.17N / mm 2 Above (e.g. 0.17N / mm 2 ~0.8N / mm 2 ), more preferably 0.18N / mm 2 Above (e.g. 0.18N / mm 2 ~0.5N / mm 2 ), more preferably 0.19 N / mm 2 Above (e.g. 0.19N / mm 2 ~0.4N / mm 2 ), most preferably 0.2N / mm 2 Above (e.g. 0.2N / mm 2 ~0.3N / mm 2 ). If the shear yield stress is less than 0.15N / mm 2 , then the laminated film cannot be given punching resistance. In contrast, if the shear yield stress is 0.15N / mm 2 The above-mentioned shear yield stress is 0.17 N / mm2, and the laminate film can be given a punching resistance. That is, the edge line marks can be suppressed, and even if the edge line marks are generated, they are generated in the area close to the end of the laminate film, so even for a narrow frame display, the image strain can be suppressed. In particular, if the shear yield stress is 0.17 N / mm2, the laminate film can be given a punching resistance. That is, the edge line marks can be suppressed, and even if the edge line marks are generated, they are generated in the area close to the end of the laminate film, so even for a narrow frame display, the image strain can be suppressed. 2The above can suppress the generation of edge line marks themselves.

[0025] It should be noted that in the present specification and claims, the shear yield stress refers to the maximum stress when the adhesive layer is displaced in the film surface direction (transverse shear), and can be measured by the method described in the examples described later.

[0026] As for the adhesive layer (or bonding layer), as long as the shear yield stress is 0.15 N / mm 2 The above may be sufficient, and a conventional adhesive or pressure-sensitive adhesive may be used. However, since edge line marks are likely to become a problem, it is preferably formed of an optically clear adhesive (OCA) used in transparent optical applications.

[0027] The optically transparent adhesive may be a conventional OCA, for example, a (meth)acrylic adhesive (or adhesive), a urethane adhesive (or adhesive), a silicone adhesive (or adhesive), a rubber adhesive (or adhesive), etc. These adhesives (or adhesives) may be used alone or in combination of two or more.

[0028] As a preferred OCA, a cured product of a curable composition is preferred, and a cured product of a curable composition containing a (meth)acrylic polymer and a crosslinking agent is particularly preferred, from the viewpoint of excellent transparency and adhesiveness and easy adjustment of the shear yield stress.

[0029] The (meth)acrylic monomers forming the (meth)acrylic polymer include cross-linkable (meth)acrylic monomers having a cross-linkable group and non-cross-linkable (meth)acrylic monomers having no cross-linkable group.

[0030] In the (meth)acrylic monomer having a crosslinkable group, examples of the crosslinkable group include a hydroxyl group, a carboxyl group, an epoxy group, and an acylamino group.

[0031] Examples of the (meth)acrylic monomer having a hydroxyl group include (meth)acrylic acid hydroxyl C such as 2-hydroxyethyl (meth)acrylate; 2-4 Alkyl esters; (poly)ethylene glycol mono(meth)acrylate, etc. (poly)C 2-4 Alkylene glycol mono(meth)acrylate; glycerol di(meth)acrylate, trimethylolethane di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol di- or tri(meth)acrylate, dipentaerythritol di- or penta(meth)acrylate, and the like.

[0032] Examples of the (meth)acrylic monomer having a carboxyl group include (meth)acrylic acid; (meth)acrylic acid carboxyl C such as β-carboxyethyl (meth)acrylate; 2-6Alkyl esters; monoesters of dicarboxylic acids and (meth) acrylic monomers having a hydroxyl group, and the like.

[0033] As a (meth)acrylic-based monomer which has an epoxy group, glycidyl (meth)acrylate etc. are mentioned, for example.

[0034] Examples of the (meth)acrylic monomer having an acyl group include: (meth)acrylamide; N,N-diC 1-4 N-substituted (meth)acrylamide such as alkyl (meth)acrylamide, etc.

[0035] Examples of the non-crosslinkable (meth)acrylic monomer include: (meth)acrylic acid linear or branched C-terminal monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and isononyl (meth)acrylate. 1-20 Alkyl esters; cyclohexyl (meth)acrylate, etc. (meth)acrylate C 5-10 Cycloalkyl esters; cross-linked cyclic (meth)acrylates such as isobornyl (meth)acrylate; (meth)acrylate C such as phenyl (meth)acrylate 6-10 Aromatic esters, etc.

[0036] These (meth)acrylic acid monomers can be used alone or in combination of two or more. These (meth)acrylic acid monomers can be (meth)acrylic acid monomers having at least a crosslinking group, or a combination of a (meth)acrylic acid monomer having a crosslinking group and a (meth)acrylic acid monomer having a non-crosslinking group. As a combination of a (meth)acrylic acid monomer having a crosslinking group and a (meth)acrylic acid monomer having a non-crosslinking group, acrylic acid C is preferred. 1-10 The combination of an alkyl ester and an acrylic monomer having a hydroxyl group and / or an acrylic monomer having a carboxyl group, particularly preferably acrylic acid C 2-8 Alkyl esters with hydroxyl C 2-6 Combinations of alkyl esters.

[0037] The weight average molecular weight of the (meth)acrylic polymer can be measured by gel permeation chromatography (GPC) or the like, and is, in terms of polystyrene, for example, 1,000 to 1,000,000, preferably 3,000 to 800,000, more preferably 5,000 to 500,000, and even more preferably 10,000 to 500,000.

[0038] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, etc. Among them, isocyanate crosslinking agents are preferred.

[0039] The isocyanate crosslinking agent is not particularly limited as long as it has a plurality of isocyanate groups, and examples thereof include aliphatic polyisocyanates [e.g., diisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate; triisocyanates such as 1,3,6-hexamethylene triisocyanate, etc.], alicyclic polyisocyanates [e.g., cyclohexane 1,4-diisocyanate, isophorone diisocyanate, hydrogenated benzylene diisocyanate, hydrogenated bis(isocyanatephenyl)methane] triisocyanates such as dicycloheptane triisocyanate, etc.], aromatic polyisocyanates [for example, diisocyanates such as phenylene diisocyanate, toluene diisocyanate, xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate, naphthalene diisocyanate, bis(isocyanatophenyl)methane (MDI), toluidine diisocyanate, 1,3-bis(isocyanatophenyl)propane, etc.; triisocyanates such as triphenylmethane triisocyanate, etc.], dimers, trimers, adducts, biuret bodies, etc. of these polyisocyanates.

[0040] These isocyanate crosslinking agents can be used alone or in combination of two or more. Among these isocyanate crosslinking agents, aromatic polyisocyanate crosslinking agents (for example, aromatic polyisocyanates such as XDI and MDI, aromatic polyisocyanates modified with alkane polyols such as trimethylolpropane, etc.) are preferred.

[0041] As for the proportion of the crosslinking agent, it can be selected from a range of about 0.01 to 10 parts by mass relative to 100 parts by mass of the (meth) acrylic polymer, for example, 0.05 to 5 parts by mass, preferably 0.1 to 3 parts by mass, more preferably 0.2 to 2 parts by mass, more preferably 0.3 to 1.5 parts by mass, and most preferably 0.5 to 1 part by mass. In the curable composition of the present disclosure, the shear yield stress of the adhesive layer can be adjusted by adjusting the proportion of the crosslinking agent within the range. If the proportion of the crosslinking agent is too small, it is difficult to adjust the shear yield stress to 0.15N / mm 2 The above possibilities.

[0042] The total proportion of the (meth)acrylic polymer and the crosslinking agent in the cured product of the curable composition may be 50% by mass or more, preferably 80% by mass or more, further preferably 90% by mass or more, more preferably 95% by mass or more, and may be 100% by mass.

[0043] The curable composition may be any of room temperature curing type, heat curing type, and light curing type. Among them, room temperature curing type is preferred from the viewpoint of being able to easily adjust the shear yield stress.

[0044] The curable composition may further include a solvent. As the solvent, conventional solvents such as water, alcohols, ketones, ethers, esters, amides, nitriles, sulfoxides, aliphatic hydrocarbons, aromatic hydrocarbons, halogenated hydrocarbons, etc. may be listed. These solvents may be used alone or in combination of two or more. Among these solvents, esters such as ethyl acetate and isopropyl acetate are preferred. With respect to the proportion of the solvent, for example, 10 to 1000 parts by mass, preferably 50 to 500 parts by mass, further preferably 100 to 400 parts by mass, more preferably 200 to 350 parts by mass, relative to 100 parts by mass of the (meth) acrylic polymer.

[0045] In addition to the (meth) acrylic polymer and the crosslinking agent, the curable composition may further include conventional additives. As conventional additives, for example, adhesion imparting agents (adhesives), viscosity modifiers, tackifiers, defoamers, fillers, lubricants, stabilizers (antioxidants, heat stabilizers, light stabilizers, etc.), flame retardants, etc. can be listed. These additives can be used alone or in combination of two or more. With respect to the total proportion of other additives, it can be 50 parts by mass or less, for example, 0.1 parts by mass to 30 parts by mass, preferably 0.5 parts by mass to 10 parts by mass, relative to 100 parts by mass of the (meth) acrylic polymer.

[0046] The total light transmittance of the adhesive layer may be 70% or more, for example 70% to 99.9%, preferably 75% to 99%, and more preferably 80% to 98%. If the total light transmittance is reduced, the punch marks will not be a problem, and the effect of the present invention may not be achieved.

[0047] In addition, in the present specification and the scope of claims, the total light transmittance can be measured in accordance with JIS K7361.

[0048] The average thickness of the adhesive layer is, for example, 1 μm to 100 μm, preferably 3 μm to 80 μm, more preferably 5 μm to 50 μm, more preferably 10 μm to 40 μm, and most preferably 20 μm to 30 μm. If the average thickness of the adhesive layer is too thin, the adhesiveness may be reduced. In addition, if it is too thin or too thick, there is a possibility that punching marks are easily generated.

[0049] It should be noted that within the scope of the present specification and claims, the average thickness of each layer can be determined by measuring any ten locations using an adhesive film thickness meter and calculating the average value.

[0050] (Base material layer)

[0051] The material of the base layer is not particularly limited, and may be any of an organic material and an inorganic material. However, since edge line marks are likely to become a problem, it is preferably formed of a transparent material.

[0052] The transparent material may be an inorganic material such as glass, but is often formed by punching. When the adhesive layer is in contact with the base layer, an organic material is preferred from the viewpoint of excellent adhesion.

[0053] Examples of the organic material include transparent resins such as cellulose ester, polyester resin, polyamide resin, polyimide resin, polycarbonate resin, and (meth)acrylic polymer. Among them, cellulose ester, polyester resin, and polycarbonate resin are preferred.

[0054] Examples of cellulose esters include cellulose acetate such as triacetyl cellulose (TAC), cellulose acetate propionate, and cellulose acetate butyrate. 3-4 Cellulose acylate, etc.

[0055] Examples of the polyester resin include polyalkylene arylate resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN).

[0056] Examples of the polycarbonate-based resin include bisphenol-type polycarbonates such as bisphenol A polycarbonate.

[0057] Among them, cellulose acetate such as TAC and polyalkylene arylate resins such as PET are preferred from the viewpoint of excellent balance in mechanical properties and transparency, and poly(C 2-4 Alkylene arylate resins.

[0058] The proportion of the transparent resin in the base material layer may be 50% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and may be 100% by mass.

[0059] When the substrate layer includes a transparent resin, the substrate layer may further include the additives exemplified as conventional additives in the curable composition of the adhesive layer. The proportion of the additives may be 50 parts by mass or less, for example, 0.1 to 30 parts by mass, and preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the transparent resin.

[0060] When the substrate layer is an organic material (particularly a polyester resin), it may be an unstretched film or a uniaxially or biaxially stretched film. When the organic material is a polyester resin, it may be a biaxially stretched film.

[0061] The base material layer may be subjected to a surface treatment (for example, a corona discharge treatment, a flame treatment, a plasma treatment, an ozone treatment, an ultraviolet irradiation treatment, etc.), or may have an easy-adhesion layer.

[0062] The total light transmittance of the substrate layer may be 70% or more, for example 70% to 99.9%, preferably 75% to 99%, and more preferably 80% to 98%. If the total light transmittance is reduced, the punch marks will not be a problem, and there is a possibility that the effect of the present invention will not be achieved.

[0063] The average thickness of the substrate layer can be selected from a range of about 10 μm to 2000 μm, for example, 20 μm to 1000 μm, preferably 30 μm to 300 μm, more preferably 50 μm to 200 μm, and most preferably 75 μm to 150 μm. If the thickness of the substrate layer is too thin, the mechanical properties of the laminated film may be reduced, and if it is too thick, it may be difficult to impart punching resistance.

[0064] (Release layer)

[0065] The laminated film of the present invention has a release layer, so during punching, the release layer is easily temporarily peeled off as the punching blade moves, and punching marks are easily generated due to the peeling of the release layer. In the laminated film of the present invention, the punching mark resistance can be improved despite the release layer.

[0066] The release layer is not particularly limited as long as it can be appropriately bonded to the adhesive layer and can be peeled off, and a commonly used release film or the like can be used.

[0067] In addition, the release layer may be formed of a resin composition comprising a thermoplastic resin and a release agent. Examples of the thermoplastic resin include polyolefin resins, polyvinyl alcohol polymers, polyester resins, polyamide resins, polyimide resins, polycarbonate resins, polyphenylene ether resins, polyphenylene sulfide resins, and cellulose esters. These thermoplastic resins may be used alone or in combination of two or more. Among these thermoplastic resins, polyC 2-4 Alkylene arylate resins.

[0068] Examples of the release agent include silicone oil, silicone resin, silicone compounds such as polyorganosiloxane having a polyoxyalkylene unit; waxes such as plant wax, animal wax, paraffin wax, polyethylene wax, ethylene copolymer wax, and polypropylene wax; 8-35 Alkali metal salts of fatty acids and other higher fatty acid metal salts; C 8-35 Fatty acid alkyl esters and other higher fatty acid alkyl esters; C 8-35Higher fatty acid amides such as fatty acid amide and alkylenebis fatty acid amide; fluorine compounds such as fluorine oil and fluorine resin, etc. These release agents can be used alone or in combination of two or more. Among them, silicone compounds are preferred.

[0069] The ratio of the release agent is, for example, 0.01 to 30 parts by mass, preferably 0.05 to 20 parts by mass, and more preferably about 0.1 to 10 parts by mass, relative to 100 parts by mass of the thermoplastic resin.

[0070] The release layer may further contain additives exemplified as conventional additives in the curable composition of the adhesive layer. The proportion of the additives may be 50 parts by mass or less, for example, 0.1 to 30 parts by mass, and preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the thermoplastic resin.

[0071] The average thickness of the release layer can be selected from a range of about 1 μm to 2000 μm, for example, 5 μm to 1000 μm, preferably 10 μm to 300 μm, and more preferably 30 μm to 200 μm.

[0072] (Characteristics of laminated films)

[0073] The laminated film of the present invention is a film for punching, and the shear yield stress of the adhesive layer is adjusted to 0.15 N / mm 2 As described above, the laminated film can be given punch cut resistance. The shear yield stress of the adhesive layer can be adjusted by appropriately selecting the material of the adhesive layer. When the adhesive layer is formed by a cured product of a curable resin composition, the material of the curable composition and / or the degree of curing can be controlled to adjust the yield stress.

[0074] The laminated film of the present invention can include other layers as long as the adhesive layer is sandwiched between the substrate layer and the release layer. As other layers, for example, hard coating, optical functional layer (anti-glare layer, polarizing layer, anti-reflection layer, refractive index adjustment layer, anti-Newton ring layer, etc.), surface protection layer (covering layer), etc. can be listed. Other layers can be arranged between the release layer and the adhesive layer, between the substrate layer and the adhesive layer, and on the substrate layer (on the opposite side of the adhesive layer) at any position, but preferably arranged between the substrate layer and the adhesive layer, on the substrate layer, and particularly preferably arranged on the substrate layer. For example, a hard coating can also be stacked on the substrate layer, and a covering layer of a punched surface can be stacked on the hard coating.

[0075] In the laminated film, the laminated film other than the release layer preferably has excellent transparency. The total light transmittance of the laminated film other than the release layer may be 70% or more, for example, 70% to 99.9%, preferably 75% to 99%, and more preferably 80% to 98%. If the total light transmittance is reduced, the punching marks will not become a problem, and there is a possibility that the effect of the present invention will not be reflected.

[0076] When the adhesive layer is in contact with the release layer, the peel strength between the adhesive layer and the release layer is, for example, 0.001 N / 50 mm to 2 N / 50 mm, preferably 0.01 N / 50 mm to 1 N / 50 mm, and more preferably 0.05 N / 50 mm to 0.5 N / 50 mm. If the peel strength is too high, there is a possibility that the demolding property is reduced, and conversely, if the peel strength is too low, there is a possibility that the workability is reduced.

[0077] In addition, in the present specification and the scope of claims, the peel strength can be measured according to the method described in JIS Z0237:2009.

[0078] The average thickness from the punched surface to the adhesive layer (or bonding layer) of the laminated film of the present invention (i.e., the average thickness of the layer between the punched surface and the adhesive layer) can be 150 μm or less (e.g., 10 μm to 150 μm), preferably 135 μm or less (e.g., 20 μm to 135 μm), further preferably 130 μm or less (e.g., 30 μm to 130 μm), more preferably 100 μm or less (e.g., 40 μm to 100 μm), and most preferably 80 μm or less (e.g., 50 μm to 80 μm). If the average thickness exceeds 150 μm, there is a possibility that the punching mark resistance is reduced.

[0079] (Method for producing laminated film)

[0080] The laminated film of the present invention can be manufactured by conventional methods, and can be manufactured by co-extrusion, coating, lamination, etc. In the case where the adhesive layer is formed by a cured product of a curable composition, the shear yield stress of the adhesive layer can be adjusted by adjusting the curing method of the adhesive layer. In the case where the curable composition is a room temperature curable composition, the shear yield stress can be adjusted, for example, by controlling the curing time (ripening time or aging time). In addition, in the case where the curable composition is a thermosetting composition, the shear yield stress can be adjusted, for example, by controlling the heating temperature and / or heating time. Furthermore, in the case where the curable resin composition is a photocurable composition, the shear yield stress can be adjusted, for example, by controlling the light irradiation amount and / or irradiation time. It should be noted that, as described above, no matter which curable composition, when the curable composition includes a crosslinking agent, the shear yield stress can be adjusted by controlling the proportion of the crosslinking agent.

[0081] [Die-cut film and its use]

[0082] The laminated film is punched into a target shape according to the application to produce a punched film (molded film). As a method for punching the laminated film, a conventional method can be used, for example, a punching machine equipped with a pinnacle knife or a Thomson knife can be used for punching. In the punching process, the adhesive layer can be punched with the surface on the side where the substrate layer is formed as the punching surface, or the adhesive layer can be punched with the surface on the side where the release layer is formed as the punching surface.

[0083] In the case where the transparency of the laminated film other than the release layer is high, the obtained punched film is preferably arranged on the display surface of the display device. As display devices, for example, there can be listed: liquid crystal display (LCD: liquid crystal display) device, cathode tube display device, organic or inorganic electroluminescence (EL: electroluminescence) display, field emission display (FED: field emission display), surface conduction electron emission display (SED: surface-conduction electron-emitter display), rear projection TV display, plasma display, display device with touch panel, touch panel display, touch sensor, etc. In these display devices, the laminated film has resistance to punching marks, so it is preferably arranged on a narrow frame display with a narrow width of the frame in the display surface. In a narrow frame display, the width of the frame can be, for example, less than 5 mm, preferably less than 3 mm.

[0084] It should be noted that the various solutions disclosed in this specification may also be combined with any other features disclosed in this specification.

[0085] Example

[0086] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to these Examples. The raw materials used in the Examples are as follows, and the obtained laminated films were evaluated by the following methods.

[0087] [raw material]

[0088] Acrylic adhesive: "Coponyl N-7520" manufactured by Mitsubishi Chemical Corporation.

[0089] Cross-linking agent: "Coronate L-45E" manufactured by Tosoh Corporation.

[0090] Release film: "COSMOPEEL TZ-600" manufactured by Toyobo Co., Ltd.

[0091] Base film: "Diafoil O321E" manufactured by Mitsubishi Chemical Corporation, average thickness 75 μm to 140 μm.

[0092] [Shearing characteristics]

[0093] The obtained laminated film is processed into Figure 1 The shape shown in the figure is used as the measurement sample. Figure 1 As shown in the side view (a) and the top view (b), the measurement sample is obtained by cutting the obtained laminated film into a width of 10 mm and processing it in a manner that the laminated structure remains only in the central part in the longitudinal direction. Figure 1 The side view (a) shows the following structure, i.e., a stacked structure remains in the central part in the longitudinal direction with a length of 10 mm, and relative to the central part, at one end, the base material layer 1 and the adhesive layer 2 are removed to expose the release layer 3, and at the other end, the release layer 3 and the adhesive layer 2 are removed to expose the base material layer 1.

[0094] The measurement sample was placed in Tensilon ("AGS-X50N" manufactured by Shimadzu Corporation), as shown in FIG. Figure 1 As shown in the side view (a) of the test sample, the exposed substrate film is stretched in the film surface direction of the test sample at a stretching speed of 5 mm / min to perform a tensile test, and the shear yield stress value applied to the adhesive layer is measured. Specifically, the maximum value or peak value of the stress at a tensile displacement of 0 mm to 1 mm is divided by the area of ​​the adhesive layer (the area of ​​the adhesive region) as the shear yield stress value.

[0095] [Edge line marks]

[0096] The obtained laminated film was punched out from the substrate film side into 90 mm × 130 mm using a punching machine ("PAC-HD" manufactured by DAITEX Co., Ltd.) with a sharp knife, a knife height of 2.2 mm, and two knives at 30°. LED lighting ("HOLOLIGHT" manufactured by PiPhotonics Co., Ltd.) was used as a light source to transmit light through the punched film, and the shadow of the film was projected onto a whiteboard to produce edge line marks on the inner side of the edge portion of the film. The produced edge line marks were evaluated according to the following indicators. As for the projection method, the punched laminated film was set between the whiteboard and the light source, and the distance between the whiteboard and the light source was adjusted to 80 cm, and the distance between the laminated film and the whiteboard was adjusted to a position where the edge line marks were most easily observed between 5 cm and 10 cm.

[0097] ○: There is absolutely no edge line mark.

[0098] Δ: The edge line mark is located at a position less than 3 mm from the end of the punched film.

[0099] ×: The edge line mark is located at a position of 3 mm or more from the end of the punched film.

[0100] Example 1

[0101] (Preparation of OCA coating solution)

[0102] An OCA coating liquid was prepared by dissolving 35 parts by mass of an acrylic adhesive and 0.15 parts by mass of a crosslinking agent in 90 parts by mass of ethyl acetate.

[0103] (Production of laminated film)

[0104] The OCA coating liquid was applied to the release surface of the release film using a Baker applicator, and dried at 120°C for 2 minutes using a drying oven to form an adhesive layer (adhesive layer) with an average thickness of 25 μm. A substrate film with an average thickness of 125 μm was bonded to the surface of the obtained adhesive layer using a pressure roller to produce a laminated film precursor. The obtained laminated film precursor was allowed to stand at 30°C and 50% RH, and the adhesive layer was cured to obtain a laminated film. At this time, the shear properties of the adhesive layer after standing for 5 days and 10 days and the edge line marks of the laminated film were evaluated.

[0105] Example 2

[0106] A laminated film was produced in the same manner as in Example 1 except that the amount of the crosslinking agent was changed to 0.3 parts by mass, and the shear properties of the adhesive layer and the edge marks of the laminated film were evaluated.

[0107] Table 1 shows the evaluation results.

[0108] [Table 1]

[0109] Table 1 (Shearing properties and edge line mark evaluation)

[0110]

[0111] It is clear from the results in Table 1 that when the shear yield stress of the adhesive layer is 0.15 N / mm 2 When the above values ​​are achieved, the generation of edge line marks is suppressed.

[0112] Example 3

[0113] A laminated film precursor was prepared in the same manner as in Example 2 except that a substrate film having an average thickness of 75 μm was used, and the obtained laminated film precursor was left to stand for 10 days under an environment of 30° C. and 50% RH to cure the adhesive layer to obtain a laminated film. The edge line marks of the laminated film were evaluated and the evaluation result was “○”.

[0114] Example 4

[0115] A laminated film precursor was prepared in the same manner as in Example 2 except that a substrate film having an average thickness of 140 μm was used, and the obtained laminated film precursor was left to stand for 10 days under an environment of 30° C. and 50% RH to cure the adhesive layer to obtain a laminated film. The edge line marks of the laminated film were evaluated and the evaluation result was “Δ”.

[0116] Industrial Applicability

[0117] The laminated film of the present invention can be used as a laminated film formed by punching, for example, it is useful as a film arranged on the display surface of various displays, and can be used as a film arranged on the display surface of PC monitors, televisions, car navigation, smart phones, tablet PCs, game consoles, etc. It can be a film pre-assembled to the display surface or a protective film for the aftermarket, but it is particularly useful as a film applied to narrow-framed displays where the presence of punching marks is easily noticeable.

[0118] Description of Reference Numerals

[0119] 1: substrate layer; 2: adhesive layer; 3: release layer.

Claims

1. A laminated film comprising a base layer, a release layer, and an adhesive layer interposed between the base layer and the release layer, The substrate layer is formed of cellulose ester, polyester resin, or polycarbonate resin. The release layer is formed of a resin composition comprising a thermoplastic resin and a silicone compound. The adhesive layer is formed of an optically transparent adhesive, and the optically transparent adhesive is a cured product of a curable composition containing a (meth)acrylic polymer and a crosslinking agent. The average thickness of the substrate layer is 10 μm to 150 μm. The average thickness of the adhesive layer is 1 μm to 100 μm, The average thickness from the punched surface to the bonding layer is less than 150 μm. Furthermore, the shear yield stress when the adhesive layer was strained at 5 mm / min in a direction parallel to the film surface was 0.15 N / mm 2 above.

2. The laminated film according to claim 1, wherein The shear yield stress is 0.17 N / mm 2 above.

3. The laminated film according to claim 1 or 2, wherein The laminated film is a film to be subjected to punching processing.

4. The laminated film according to claim 1 or 2, wherein The laminated film is a punched film obtained by a punching process. 5 . A method for producing a punched film, the method comprising punching the laminated film according to claim 1 or 2 to produce a punched film. 6 . A display device comprising the punched film according to claim 4 on a display surface.

7. The display device according to claim 6, wherein: The display device is a narrow-frame display.

8. A method for improving the punch mark resistance of a laminated film, the method comprising adjusting the shear yield stress of the laminated film comprising a substrate layer, a release layer, and an adhesive layer sandwiched between the substrate layer and the release layer to 0.15 N / mm2 when a strain of 5 mm / min is applied to the adhesive layer in a direction parallel to the film surface 2 As described above, the punching resistance of the laminated film is improved. The substrate layer is formed of cellulose ester, polyester resin, or polycarbonate resin, and has an average thickness of 10 μm to 150 μm. The average thickness of the adhesive layer is 1 μm to 100 μm, The average thickness from the punched surface to the bonding layer is less than 150 μm. The release layer is formed of a resin composition comprising a thermoplastic resin and a silicone compound. The adhesive layer is formed of an optically transparent adhesive that is a cured product of a curable composition containing a (meth)acrylic polymer and a cross-linking agent.

Citation Information

Patent Citations

  • Transparent laminate film

    JP2015098123A

  • Adhesive composition for polarization plates, adhesive sheet for polarization plates, polarization plate with adhesive layer, laminate body and flat panel display

    CN105308143A

  • Adhesive selection method, adhesive complex and method for production of the adhesive complex

    JP2020193275A